Lsm14b controls zebrafish oocyte growth by regulating polyadenylation of the mRNA poly(A) tail - Wu, Xingxing; Peng, Xixia; Deng, Tingting; Peng, Wanjun; Hu, Bing; Nie, Guohui (Frontiers in Marine Science, 2024)
Lsm14b (LSM family member 14b) is a messenger ribonucleoprotein (mRNP) and a widely present component in eukaryotes. Lsm14b participates in oocyte development by regulating mRNA translation, however, the specific translational regulatory mechanisms remain unclear.Here, we explore the function of Lsm14b during early oocyte development and identify specific translational regulatory mechanisms. We established female-infertile lsm14b mutant zebrafish using CRISPR/Cas9. Histological examination showed that the oocyte development in the mutant zebrafish was arrested at the primary growth (PG) stage. The gene set enrichment analysis (GSEA) analysis of the transcriptome revealed that signaling pathways associated with mRNA translation suppression and mRNA poly(A) tail shortening were significantly downregulation in the mutant.The poly(A) tail length (PAT) assay confirmed the lengthen of mRNA poly(A) tail of the oocyte development-related genes zar1 and figla in the mutant. Further studies have suggested that the loss of Lsm14b triggers the unfolded protein response (UPR), which is related to abnormal translation inhibition. Our results demonstrate that Lsm14b assists in maintaining the translationinhibited state of mRNA by regulating the length of the mRNA poly(A) tail in zebrafish early oocytes, which ensures that the mRNA synthesized and stored during the growth stage of oocytes, is necessary for the normal growth and development of oocytes.